Laboratory monitoring of UFH in different settings (DEXHEP study): association between anti-Xa levels, PF4 plasma levels and dextran sulfate - SAVARD, Philippe; Curis, Emmanuel; Gouin-Thibault, Isabelle; Toussaint-Hacquard, Marie; Delassasseigne, Céline; Bauters, Anne; Flaujac, Claire; Mouton, Christine; Lecompte, Thomas; demaistre, emmanuel; Lasne, Dominique; Siguret, Virginie (Thrombosis and Haemostasis)
Background: Chromogenic anti-Xa assay is currently used in the management of patients on unfractionated heparin (UFH). It has been shown that inter-assay variability in anti-Xa levels can be explained in part by the presence or absence of dextran sulfate (DXS) in the reagents. DXS has the ability to dissociate UFH from neutralizing proteins, including platelet factor 4 (PF4). Aims: investigate whether PF4 plasma levels along with the presence/absence of DXS in anti-Xa reagents are associated with variations in UFH anti-Xa levels in different clinical situations Methods. In the prospective multicenter study DEXHEP-NCT04700670, critically ill patients on UFH therapy (4 groups) were recruited. Blood was collected into citrate and CTAD tubes. Chromogenic anti-Xa levels were assessed using 7 reagent/analyzer combinations including 2 without DXS. Plasma PF4 was measured by ELISA (ZymutestTM-PF4-Hyphen-Biomed). Results: 144 patients were analysed: average PF4 levels in citrate plasma samples were consistently higher than in CTAD ones (206 vs 46 ng/mL, p<10-4), regardless the patient group. Using a linear mixed-effect model, we found a significant effect of both DXS and PF4 on anti-Xa level, with a significant interaction term (p<10-4). Considering the 0.3-0.7 IU/mL therapeutic range, agreement between anti-Xa values (Liquid-anti-Xa/DXS-free vs Biophen-LRT/DXS) was observed in roughly two-thirds of patients. Conclusion: PF4 levels slightly affects anti-Xa levels, the use of CTAD tubes minimizing the effect. However, PF4 levels do not fully explain the differences of anti-Xa levels observed in the presence or absence of DXS, which has a greater effect. Anti-Xa assays require better standardization.